2020
DOI: 10.1093/jas/skaa154
|View full text |Cite
|
Sign up to set email alerts
|

Indirect predictions with a large number of genotyped animals using the algorithm for proven and young

Abstract: Reliable single-nucleotide polymorphisms (SNP) effects from genomic best linear unbiased prediction BLUP (GBLUP) and single-step GBLUP (ssGBLUP) are needed to calculate indirect predictions (IP) for young genotyped animals and animals not included in official evaluations. Obtaining reliable SNP effects and IP requires a minimum number of animals and when a large number of genotyped animals are available, the algorithm for proven and young (APY) may be needed. Thus, the objectives of this study were to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…The G −1 for JER, HOL, JER_HOL, and MIX were obtained using APY. The IP from ssGBLUP have been shown to be stable when using different core animals as long as the size of the core is at least equal to the number of eigenvalues required to explain 98 to 99% of the genomic variation (Garcia et al, 2020), which was the case in this study.…”
Section: Methodsmentioning
confidence: 74%
“…The G −1 for JER, HOL, JER_HOL, and MIX were obtained using APY. The IP from ssGBLUP have been shown to be stable when using different core animals as long as the size of the core is at least equal to the number of eigenvalues required to explain 98 to 99% of the genomic variation (Garcia et al, 2020), which was the case in this study.…”
Section: Methodsmentioning
confidence: 74%
“…Including all of these animals in the main routine evaluation may not be reasonable because of the computing cost. Garcia et al (2020) reported that the accuracy of IGP was as high as that of GEBV in American Angus data, where about 70% of the genotyped animals had phenotypes. In that study, they did not investigate which animals should be included in the computation of GEBV and IGP or how GEBV for those genotyped animals affect accuracy and bias in IGPs when those genotyped animals have neither phenotype nor progeny.…”
Section: Graphical Abstract Summarymentioning
confidence: 99%
“…The statistical model for pig traits was as in Steyn et al (2020) , for beef traits was as in Garcia et al (2020) , and for broiler chicken traits was as in Lourenco et al (2015a) . The (co)variance components used in all analyses were provided by PIC, Angus Genetics Inc., and Cobb-Vantress.…”
Section: Methodsmentioning
confidence: 99%